The Ethical Perspective of Millennial Accountants in Responding to Opportunities and Challenges of Blockchain 4.0 - Sendy Dwi Haryanto; Erina Sudaryati (Journal of Accounting and Investment, 2020)
Research aims: This study aims to provide a perspective on the professional ethics of a millennial accountant in applying blockchain technology to improve his professionalism, and discusses the issue of blockchain ethical challenges for an accountant's professionDesign/Methodology/Approach: A research approach is a qualitative approach with interviews with the millennial accountants, namely millennial corporate accountants, millennial research accountants, and millennial internal auditors.Research findings: The study results indicated that a millennial accountant in the 4.0 revolution era is required to adapt to technology. The blockchain technology extends the ethical approach to utilitarianism to a broader social level with decentralization in serving stakeholders’ information needs. Blockchain changes the task of millennial accountants who previously produced information into information evaluators. Millennial accountants must change their mindset to absorb the essence of the accountant's code of ethics and harmonize ethical values. It is the basis for acting ethically to avoid the moral dilemma of technological adaptation.Theoretical contribution/Originality: The contribution of this research for accountants is to build a moral-ethical perspective in adopting blockchain technology that prevents potential impacts on business and society and to describe the challenges that the accounting profession will face in adopting blockchain in the industrial revolution 4.0.Practitioner/Policy implication: The implications of this study illustrate that the blockchain can change perspectives in real-time accounting to reduce practitioners' mistakes from the accounting profession by considering the ethical and moral aspects of a millennial accountant.Research limitation/Implication: The limitation of this study is the first; it has not yet deepened the three challenges faced by millennial accountants in the revolutionary 4.0 era. Secondly, millennial educator accountants have not yet to be involved as interviewees.